Pernikahan Lintas Iman Dalam Konteks Gereja Katolik:Analisis Hukum Kanonik Dan Upaya Rekonsiliasi - Rillyanugraha, Richardo; Endi, Yohanes (Jurnal Masalah Pastoral, 2024)
This article discusses interfaith marriages in the context of the Catholic Church, especially from the perspective of canon law and reconciliation efforts. The Catholic Church recognizes the validity of interfaith marriages under certain conditions, although it does not consider them sacraments. Through an analysis of canon law, requirements such as dispensation from the bishop, guarantees of educating children in the Catholic faith, and adapted marriage procedures are discussed. This article also explores the challenges of interfaith marriages, such as the potential for conflict due to differences in religious beliefs and practices. Furthermore, this article describes reconciliation efforts carried out by the Catholic Church, such as inter-faith dialogue to build mutual understanding, special pastoral formation for interfaith couples, as well as a more inclusive approach involving figures from other religions. The main goal of this effort is to help couples build strong commitment, overcome challenges wisely, and create a harmonious and loving family environment. This article highlights the Catholic Church's efforts to balance maintaining the integrity of Catholic teachings and values ​​by demonstrating openness and tolerance towards diversity of beliefs in an increasingly pluralistic modern society.